Literature Review: Literasi Digital Sebagai Pemicu Kemampuan Berpikir Kritis Mahasiswa - Ilhamurrahman M Hubaib; Indrawati Syamsuddin; Wirana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to comprehensively examine digital literacy as a driver of university students’ critical thinking skills through a literature review method. Digital literacy plays an important role in strengthening students’ critical thinking. It helps enhance their ability to evaluate information, assess multiple sources, recognize bias, and make decisions based on strong evidence. In addition, integrating digital literacy with technology-enhanced learning approaches supports the development of critical thinking. Nevertheless, several studies also show that while digital literacy can trigger improvements in students’ critical thinking, better strategies are needed to raise it from a moderate to a strong level, along with targeted teaching strategies and strong institutional support to maximize critical thinking skills. Digital literacy is a central factor in fostering students’ critical thinking and should be systematically integrated into higher education curricula to enhance learning and equip students to face the challenges of the digital era.